2021
DOI: 10.1016/j.medj.2020.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Kidney Function Indicators Predict Adverse Outcomes of COVID-19

Abstract: Background The coronavirus disease 2019 (COVID-19) is an emerged respiratory infectious disease with kidney injury as a part of the clinical complications. However, the dynamic change of kidney function and its association with COVID-19 prognosis are largely unknown. Methods In this multicenter retrospective cohort study, we analyzed clinical characteristics, medical history, laboratory tests, and treatment data of 12,413 COVID-19 patients. The patient cohort was strati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(70 citation statements)
references
References 33 publications
4
53
0
1
Order By: Relevance
“…A part of the baseline data in this manuscript have been used in our previous articles. 30 , 31 , 32 , 33 …”
Section: Methodsmentioning
confidence: 99%
“…A part of the baseline data in this manuscript have been used in our previous articles. 30 , 31 , 32 , 33 …”
Section: Methodsmentioning
confidence: 99%
“…Our results revealed that abnormal CT findings were more prominent in patients with AF. Recently studies have shown that elevated troponin, D-dimer, urea, CRP concentrations, lower albumin levels and lower lymphocyte counts were associated with severe complications of COVID-19 [ [31] , [32] , [33] ]. The results of our study have confirmed previous findings on these biochemical markers.…”
Section: Discussionmentioning
confidence: 99%
“…The study was limited by its low sample size of 86 patients, but found no benefit of LPV/r in the rate of positive-to-negative conversion of SARS-CoV-2 nucleic acid or improvement in symptoms or imaging. In fact, the therapy only increased adverse events from primarily diarrhea and loss of appetite in the LPV/r arm [ 42 ].…”
Section: Treatment Optionsmentioning
confidence: 99%
“…Favipiravir and umifenovir are broad antivirals approved in countries outside the USA that were used as anti-influenza agents. Both drugs have had limited clinical data supporting their use, although there has been some in vitro data [ 40 , 42 , 95 , 96 ]. Sofosbuvir/daclatasvir is a treatment for hepatitis C infection that has also been found to bind to SARS-CoV-2 [ 97 ].…”
Section: Treatment Optionsmentioning
confidence: 99%